(untitled) (Research, Society and Development, 2021)
This research brings reflections about the diversification of a rural property in relation to a property that invests in tobacco monoculture. Both properties are located in the northern region of the municipality of Agudo, Rio Grande do Sul, Brazil. Its general objective was to investigate what each one produces for their self-sufficiency and what / how much they buy, seeking to identify the benefits that the diversification of agricultural production brings to the family, both financial and nutritional, directly influencing the individual’s health. In order for the research to be carried out, it was decided to collect the data through direct observation on the properties as well as informal conversation with the owners to understand the differences and the motivations that maintain these aspects. The data found point to a greater financial freedom and nutritional quality for a family that invests in the diversification of the property in relation to the family that is dedicated to the cultivation of tobacco and is financially dependent on tobacco companies.